A Regression Tree for Identifying Risk Factors for Fear of Falling: The International Mobility in Aging Study (IMIAS). (8th February 2019) - Curcio, Carmen-Lucia; Wu, Yan Yan; Vafaei, Afshin; Barbosa, Juliana Fernandez de Souza; Guerra, Ricardo; Guralnik, Jack; Gomez, Fernando
Abstract: Background: We determine the best combination of factors for predicting the risk of developing fear of falling (FOF) in older people via Classification Regression Tree (CaRT) analysis. Methods: Community-dwelling older adults living in Canada, Albania, Brazil, and Colombia were from International Mobility in Aging Study (IMIAS). In 2014, 1, 725 participants (aged 65–74) were assessed. With a retention rate of 81%, in 2016, 1, 409 individuals were reassessed. Risk factors for FOF were entered into the CaRT: age, sex, education, self-rated health, comorbidity, medication, visual impairment, frailty, cognitive deficit, depression, fall history, Short Physical Performance Battery (SPPB), walking aid use, and mobility disability measured by the Nagi questionnaire. Results: The classification tree included 12 end groups representing differential risks of FOF with a minimum of two and a maximum of five predictors. The first split in the tree involved impaired physical function (SPPB scores). Respondents with less than 8 in SPPB score and mobility disability had 82% risk of developing FOF at the end of 2-year follow-up. Between 23.2% and 82.3% of the risk of developing FOF in 2 years of follow-up were explained by only five variables: age, sex, self-rated health, functional impairment measured by SPPB, and mobility disability. In those with no functional impairment or mobility disability, levels of education, sex, and self-rated health were important predictors of FOF in the future. Conclusion: This classification tree included different groups based on specific combinations of a maximum of five easily measurable predictors with emphasis on impaired physical functioning risk factors for developing FOF.